Pemikiran Hermeneutika Rudolf Bultmann: Eksistensialisasi dan Demitologisasi - Nur Shofa Ulfiyati (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2020)
Myth is an expression of a certain understanding of human existence. Sometimes mythology is often regarded as a primitive science or knowledge, which aims to explain the symptoms and events that are rare, strange or surprising and which people consider to be the result of evil spirits. This paper describes the existence of myths in the scriptures which should not be discarded, but rather given an explanation so that it can be understood for the present through the concept of Demitologization. Demythologization is the interpretation of parts of the Bible that are considered mythological by emphasizing the existential truths contained in the myth. According to Bultman, modern humans find it difficult to understand the preaching of the new agreement. In this case, Rudolf Bultmann as a theologian tried to think seriously about how a holy book from the pre-Muslim era could be accepted by modern humans so that he offered a demythologizing concept so that humans could believe what was in the scriptures.